Mozambique’s Coming Natural Resource Boom Expectations, Vulnerabilities, and Policies for Successful Management - Biggs, Tyler (USAID, 2012)
Mozambique is set to become a world-class natural resource exporter with projections indicating that it will experience rapid increases in windfall revenues over the next several decades and well beyond. While this is welcome news for a low-income country with a substantial proportion of the population below the poverty line, it foreshadows some economic management problems ahead. The main concern is the poor economic record of many other lowincome countries with large natural resource endowments. It is remarkable how often these countries have experienced inferior rates of growth compared with countries lacking such endowments. This pattern, known as the ―natural resource curse,‖ has been documented in empirical research across a wide sample of nations.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural disasters / desastres naturais

Capacity Strengthening in the Least Developed Countries (ldcs) for Adaptation to Climate Change (clacc): Climate Change and Health in Mozambique - Bambaíge, Albertina João; Cuamba, Boaventura; Hauengue, Maria dos Anjos (International Institute for Environment and Development (IIED), 2008)
The relationship between climate change and its effects on human health has been widely studied. Increases in temperature and variations in precipitation can exacerbate a number of human diseases including respiratory infections, malnutrition, vector and water borne diseases such as malaria and cholera. Besides all efforts undertaken by the Mozambican Government to reduce poverty and meet the MDGs targets, it is clear that climate change effects will influence negatively in meeting these targets. Damages caused by floods in Mozambique undermine economic growth rates of the country. Mainstreaming climate change adaptation into government policies would strengthen the capacity of the country to deal with climate change impacts. Climate change is a reality and the impacts on health are great with the poor at most risk. Efforts must be done nationally at all levels to come up with a proactive approach since all actors in the Mozambican society are directly or indirectly affected. This must include clear policies and strategies to deal with impacts of climate change on health; intersectoral approaches for strengthening the implementation of these policies and a greater support from those wealthy in resources and knowledge for minimizing the risks and increase community's adaptation capacity. The case study included in this country report highlights the relationship between climate change and human health through an analysis of malaria and cholera data taking the example of the 2000/2001 floods, which were considered the worst in the last fifty years. Adaptation practices and the adaptive capacity of the country during floods periods, policies and strategies are also discussed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; government policy / politica governamental; health / saúde; institutions / instituições; natural disasters / desastres naturais

Mozambique | Tropical Cyclone Eloise Response Situation Report #1 | 25 January - 12 February 2021 - Mozambique
English Situation Report on Mozambique about Camp Coordination and Camp Management, Health, Epidemic, Flood and more; published on 12 Feb 2021 by IOM
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; GP - Sofala; L - english / inglês; natural disasters / desastres naturais